Synthesis and characterization of novel dumbbell shaped copolymers poly(ethylene oxide)x-b-polystyrene-b-poly(ethylene oxide)x with tunable side arms by combination of efficient thiol-ene addition reaction with living polymerization mechanism. Issue 41 (7th May 2015) - Chen, Lingdi; Huang, Jian; Wang, Xuepu; Lu, Chengjiao; Zhang, Hongdong; Wang, Guowei
<x xml:space="preserve">Abstract</x> A series of well-defined dumbbell shaped copolymers consisting of PEO and PS segments were successfully synthesized by LAP and ROP mechanisms and the efficient thiol-ene addition reaction. This versatile synthetic route might be used to synthesize other similar copolymers.